Age-dependent associations among insomnia, depression, and inflammation in nurses. Issue 8 (3rd August 2021) - Walker, Jamie L.; Slavish, Danica C.; Dolan, Megan; Dietch, Jessica R.; Wardle-Pinkston, Sophie; Messman, Brett; Ruggero, Camilo J.; Kohut, Marian; Borwick, Joshua; Kelly, Kimberly; Taylor, Daniel J.
Abstract: Objective: Insomnia and depression have been inconsistently associated with inflammation. Age may be one important moderator of these associations. This study examined associations between insomnia and depression with inflammatory biomarkers in nurses and how these associations varied by age. Design: Participants were 392 nurses ages 18-65 ( M age = 39.54 years ± 11.15, 92% female) recruited from two hospitals. Main outcome measures: Participants completed surveys to assess insomnia and depression symptoms. Serum samples were obtained and analysed for inflammatory biomarkers interleukin-6 (IL-6), C-reactive protein (CRP), interleukin-1 beta (IL-1β), and tumour necrosis factor alpha (TNF-α). Results: Neither insomnia nor depression symptoms were associated with inflammatory biomarkers. Older age was associated with higher IL-1β, and age moderated the effects of depression symptoms on CRP and TNF-α: Greater depression symptoms were associated with higher CRP ( b = .14, p = .017) and TNF-α ( b = .008, p = .165) among older nurses only. Conclusion : Results suggest older nurses with higher depression symptoms may be at increased risk for elevated inflammation. Interventions should consider the role of age-related processes in modifying health and well-being. Given relatively low levels of depression in the current sample, future studies should replicate results in clinical and non-nurse samples.